Family Coping Strategies and Quality of Life of Patients with Type-2 Diabetes Mellitus in Primary Health Care in Indonesia - Setyoadi, Setyoadi; Efendi, Ferry; Haryanto, Joni; Rosyidawati, Fitri; Dima Kristianingrum, Niko; Srihayati, Yati; Dewi Sartika Lestari Ismail, Dina (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2023)
Background: The intricate caregiving responsibilities undertaken by family caregivers in the care of patients with chronic diseases induce stress, potentially reducing the family’s ability to provide effective care. In instances where family caregivers of patients with type-2 diabetes mellitus (T2DM) are unable to employ effective coping mechanisms, there exists the potential for an adverse impact on the patient’s quality of life. Purpose: This study aimed to analyze the relationship between family coping strategies and the quality of life of patients with T2DM undergoing treatment in primary health care in Malang, Indonesia. Additionally, it sought to investigate the influence of demographic factors on both family coping strategies and the quality of life of these patients.Methods: The study employed an observational analytic design with a cross-sectional approach. The participants included 327 individuals with T2DM and 327 family caregivers, selected from 16 primary healthcare centers using cluster random sampling techniques. Data were collected using the COPE Brief questionnaire to assess coping strategies and the DQOL (Diabetes Quality of Life) questionnaire to measure the quality of life. Statistical analysis was conducted using the Spearman rank test and multivariable logistic regression. Results: The findings of the study revealed that a majority of family caregivers employed adaptive coping strategies (93.9%), while a significant proportion of individuals with T2DM reported having a good quality of life (84.1%). The analysis demonstrated a positive relationship between family coping strategies and the quality of life among T2DM patients. Specifically, better family coping strategy was associated with higher quality of life in T2DM patients (p=0.000; r=0.447; α=0.05). Also, a comprehensive demographic analysis revealed that education significantly influences both the variables of family coping strategies and patient quality of life, with odds ratios of 1.284 and 1.561, respectively.Conclusion: The research findings emphasize the mutual influence between family coping strategies and quality of life of T2DM patients. Nurses should prioritize attention to demographic factors such as education, age, gender, and duration of diabetes to enhance family coping strategies and improve the patients’ quality of life.